Phenomenology: systematic aspects and epistemological prospects (Actual Problems of Mind, 2017)
The paper presents a new approach in the modern theoretical investigations based on the principles of a systematic analysis of reality with due account for a model of «incorporated observer». The author considers the main advantage of the principle to be an «informational» image of reality.
Keywords: Phenomenology; information; philosophy of language; unity of mental and physical; supervenience